Poetyka autentyczności czyli o autobiografizmie w twórczości ks. Jana Twardowskiego - Marcjan, Maria (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2003)
The work is an analisis different ways occurrence of autobiography in poetic literary the priest, Jan Twardowski. Apart from remembrance formulation and repetitions some themes considers stylizing formulations, a part of titles, dedications and aphorisms. It is important what is the attitude of the receiver who looks for truth and authenticity in poetry.